Sequential hepatic and pulmonary resections for metastatic colorectal cancer - Lehnert, Thomas; Knaebel, Hanns-Peter; Dueck, Margret; Bülzebruck, Heinrich; Herfarth, Christian (The British journal of surgery, 2003)
Background: Resection of pulmonary or hepatic colorectal metastases is associated with a 5-year survival rate of 25-40 per cent. This report analyses outcome following sequential resection of colorectal metastases to both organs. Methods: Seventeen patients with histologically confirmed colorectal adenocarcinoma and resection of liver and lung metastases were identified from a prospective database. Results: The median interval between resection of the primary tumour and first metastasis was 21 (range 0-64) months. The interval between resection of the first and subsequent metastases was 18 (range 1-74) months. No patient died in the postoperative period and there were two perioperative complications. The overall survival rate in 17 patients was 70 per cent at 2 years from resection of metastasis to the second organ, but the disease-free survival rate at 2 years was only 24 per cent. Conclusion: Although few long-term survivors were observed in this small series, sequential resection of hepatic and pulmonary metastases is warranted in a highly selected group of patients. © 1999 British Journal of Surgery Society Ltd
First published: 02 January 2003
Gesehen am 28.12.2020